Observations on the infection and rotting of apples var. Bramley's Seedliong by Diaporthe perniciosa - Ayub, A. Nawawi Hoji; Swinburne, Terence R. (Wiley, 1970)
In N. Ireland Diaporthe perniciosa March is a common inhabitant of the dead wood of Bramley's Seedling apple trees, and its pycnospores, extruded throughout the growing season, are responsible for fruit infections which result in stalk‐end rots during storage. Pycnidia were produced in culture only after exposure to light, near‐UV radiation being particularly favourable. The carbon source in the medium influenced pycnidia production: high yields were obtained where mannitol was used. Only a‐spores germinated under the conditions tested, giving optimum germination at 25 d̀C. in a water film. No germination occurred at less than 98% R.H. Germ tubes and hyphae developed appressoria after germination on artificial surfaces but on apple skin most spores produced only a protuberance from which penetration hyphae developed directly. The cuticle and epidermal cells of apples of all ages were penetrated within a few days of inoculation. Intact surfaces and lenticels were penetrated equally. Susceptibility to further rotting increased with age of the fruit. Apples loaded with spores early in the season rotted later than similar apples loaded just before picking. Polygalacturonase was detected in sap expressed from rotted apples of various ages, the level of activity being correlated with the susceptibility of the fruit. Copyright © 1970, Wiley Blackwell. All rights reserved